Restriction map of corynebacteriophages beta c and beta vir and physical localization of the diphtheria tox operon. - Costa, J J (1981)
The BamHI, EcoRI, HindIII, and KpnI restriction endonuclease maps of corynebacteriophage beta c and beta vir were constructed. beta vir appeared to be identical to beta c, except for an approximate 1-kilobase deletion that removed a BamHI site, two KpnI sites, and three EcoRI restriction sites. The diphtheria tox operon was located by hybridizing in vitro 32P-labeled tox messenger ribonucleic acid to blots of endonuclease-digested beta deoxyribonucleic acids. The messenger ribonucleic acid probe was found to hybridize to a 2.1-kilobase region of the beta genome. Since approximately 1.9 kilobases is required to encode prodiphtheria toxin, the data presented strongly suggest that the tox operon of beta is monocistronic.